2017
DOI: 10.3758/s13421-017-0692-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of context in item-based directed forgetting: Evidence for “one-shot” context storage

Abstract: The effects of context on item-based directed forgetting were assessed. Study words were presented against different background pictures and were followed by a cue to remember (R) or forget (F) the target item. The effects of incidental and intentional encoding of context on recognition of the study words were examined in Experiments 1 and 2. Recognition memory for the picture contexts was assessed in Experiments 3a and 3b. Recognition was greater for R-cued compared to F-cued targets, demonstrating an effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 41 publications
6
24
2
Order By: Relevance
“…At first glance, the finding that the intention to remember affected item-context bindings seems to contradict a recent study by Burgess et al (2017) where Directed Forgetting did not affect context information. Burgess et al (2017) presented words against different background pictures of landscapes which were then followed by a remember or a forget instruction.…”
Section: One-shot Context Storagecontrasting
confidence: 80%
See 1 more Smart Citation
“…At first glance, the finding that the intention to remember affected item-context bindings seems to contradict a recent study by Burgess et al (2017) where Directed Forgetting did not affect context information. Burgess et al (2017) presented words against different background pictures of landscapes which were then followed by a remember or a forget instruction.…”
Section: One-shot Context Storagecontrasting
confidence: 80%
“…At first glance, the finding that the intention to remember affected item-context bindings seems to contradict a recent study by Burgess et al (2017) where Directed Forgetting did not affect context information. Burgess et al (2017) presented words against different background pictures of landscapes which were then followed by a remember or a forget instruction. The authors demonstrated Directed Forgetting effects for the target items (the words; recognition for To-beremembered words was better than for To-be-forgotten words) but not the background pictures.…”
Section: One-shot Context Storagecontrasting
confidence: 80%
“…The parameters were g base = 0.4, g draw = 0.38, w = 20, u 1 = 0.28, u 2 = 0.12, c = 0.7, and criterion test = 1. spaced strengthening but not massed strengthening. They explained this using the one-shot hypothesis of context storage, according to which a maximum amount of context information can be stored during any given study trial (see also Burgess, Hockley, & Hourihan, 2017). Consequently, presenting an item for 2 or 6 s will result in the same amount of context information being stored.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there has been extensive research on the role of context in recall and recognition [12,13] under a number of contexts such as cued recognition and forget scenarios. These studies suggest that the brain uses the 1-2 seconds in a recall task to store the existing contextual information [14], indicating that viewing scenes in a VW environment may utilize context effects without any the for lengthy viewing. Several knowledge acquisition and training approaches utilize the method of loci [15,16].…”
Section: Memory and 3d Virtual Worldsmentioning
confidence: 96%
“…The same avatar is depicted when a role is engaged in another activity, and the same desk space is used for the individual tasks s/he performs. In this way, the concepts of visual context and spatial location are used to embody real life concepts and implement visual priming to enhance recall [14]. Other process elements such as IT systems and data elements are represented in an abstract form based on BPMN-style notational elements, since these elements do not have any physical discriminatory characteristics.…”
Section: Design Of the Training Environmentmentioning
confidence: 99%